2021
DOI: 10.3390/cancers13040811
|View full text |Cite
|
Sign up to set email alerts
|

Serum CYFRA 21.1 Level Predicts Disease Course in Thyroid Cancer with Distant Metastasis

Abstract: Background: Serum Cyfra 21.1, the soluble fragment of CK19, has been used as a prognostic tumor marker in various cancers, indicating poor tumor differentiation and increased metastasis. Methods: We analyzed the serum Cyfra 21.1 level in 51 consecutive patients with thyroid cancer manifesting distant metastasis treated with prior total thyroidectomy. Serum Cyfra 21.1 levels of 26 thyroid cancer patients without metastasis and 50 healthy individuals were used for comparison. Results: Higher serum Cyfra 21.1 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The key difference in the present work was the precise matching of preoperatively confirmed metastatic LNs with those evaluated during surgery; this enabled more accurate interpretation of the final pathologies and the washout Tg and CYFRA 21-1 levels. Many studies have suggested that the CYFRA 21-1 level is a useful prognostic factor in patients with various cancers, but most have only measured serum levels of this marker 21 , 22 , 30 , 31 . The washout CYFRA 21-1 levels of LN FNA samples have seldom been assayed; no useful diagnostic/prognostic cutoff has yet been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The key difference in the present work was the precise matching of preoperatively confirmed metastatic LNs with those evaluated during surgery; this enabled more accurate interpretation of the final pathologies and the washout Tg and CYFRA 21-1 levels. Many studies have suggested that the CYFRA 21-1 level is a useful prognostic factor in patients with various cancers, but most have only measured serum levels of this marker 21 , 22 , 30 , 31 . The washout CYFRA 21-1 levels of LN FNA samples have seldom been assayed; no useful diagnostic/prognostic cutoff has yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that serum levels of CYFRA 21-1 are prognostic of thyroid cancer progression 21 , 22 . Jeong et al demonstrated the utility of such measurements in thyroid cancer patients with distant metastases who exhibited disease progression 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lei et al developed an ICS test based on fluorescent microspheres for the rapid and quantitative detection of urinary Cyfra 21-1, which is in use for the diagnosis and prognostic monitoring of bladder cancer, confirming the reliable application of immunochromatographic technology in detecting Cyfra 21-1 levels ( Lei et al, 2019 ). Recent studies have also shown that an increased Cyfra 21-1 level is associated with distant metastasis and tumor progression of thyroid cancer ( Giovanella et al, 2017 ; Jeong et al, 2021 ). Determination of the Cyfra 21-1 level in the eluent from a fine-needle aspiration of the lymph node may improve the diagnosis of lymph node metastasis in patients with differentiated thyroid cancer ( Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%